2008
DOI: 10.1111/j.1600-0714.2008.00687.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between enzyme production, germ tube formation and susceptibility to fluconazole in Candida species isolated from patients with denture‐related stomatitis and control individuals

Abstract: The results reinforced the idea that C. albicans is the most frequent and can be the most pathogenic yeast in oral candidosis. However, the strains isolated from DRS patients and healthy individuals showed the same virulence factors. It seems that several virulence attributes are involved in the infective process but no single factor contributes to Candida virulence. Candida dubliniensis was absent in the oral cavity of individuals with and without DRS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
46
0
8

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 24 publications
6
46
0
8
Order By: Relevance
“…Germ tube formation is one of the important mechanisms of pathogenicity of C. albicans (Pinto et al, 2008). Most antifungal drugs are germ tube formation inhibitors (Ellepola and Samaranayake, 1998).…”
Section: Effect Of Eugenol and Linalool On Germ Tube Formation By C mentioning
confidence: 99%
“…Germ tube formation is one of the important mechanisms of pathogenicity of C. albicans (Pinto et al, 2008). Most antifungal drugs are germ tube formation inhibitors (Ellepola and Samaranayake, 1998).…”
Section: Effect Of Eugenol and Linalool On Germ Tube Formation By C mentioning
confidence: 99%
“…Though our results show that GT development is very sensitive to the antifungal treatment, it should not be considered as an only parameter or predictor of fungal virulence. The strong correlation observed in the fungus virulence factors involved in infections shows that an individual evaluation of them would be a simplification of the analysis, considering that not all the factors are expressed in infections or necessarily in a particular stage of infection (29). Ellepola et al have shown that a combined treatment with antifungics would act as adjuvants in denturerelated oral candidiasis and would allow diminishing (7).…”
Section: Determination Of Phospholipase Activity (Pl)mentioning
confidence: 99%
“…W badaniach Ciesielskiej et al [20] odsetek zakażenia grzybiczego błony śluzowej jamy ustnej u użytkowników protez ruchomych był nieco mniejszy i obejmował 72% przypadków. Pinto et al [21] w badaniach przeprowadzonych wśród 140 pacjentów użytkujących ruchome uzupełnienia protetyczne odtwarzające braki zębowe w szczęce stwierdzili wzrost grzybów drożdżopo-dobnych u 92,9% osób, u których rozpoznano stomatopatię protetyczną, przy czym dominującym gatunkiem (87,7%) była Candida albicans. W identycznej pod względem liczebności grupie pacjentów użytkujących ruchome uzupełnienia protetyczne (70 osób), u których nie stwierdzono stomatopatii protetycznej, wzrost kolonii grzybów drożdżopodobnych obserwowano w 58,6% przypadków, a dominującym patogenem (61%) była Candida albicans.…”
unclassified
“…Badania te sugerują możliwość wnikania i penetracji tych form przez błonę śluzową organizmu. Pinto et al [21] oceniając aktywność fosfolipazy u 140 użytkowników protez płytowych, wykazali 100% sekrecję tych hydrolaz w grupie pacjentów, u któ-rych rozpoznano stomatopatię oraz 97,9% przypadków uwalniania tych enzymów wśród osób, u któ-rych nie stwierdzono stomatopatii protetycznej.…”
unclassified
See 1 more Smart Citation